2019
DOI: 10.1002/fld.4776
|View full text |Cite
|
Sign up to set email alerts
|

On the role of (weak) compressibility for fluid‐structure interaction solvers

Abstract: In the present study, a weakly compressible formulation of the Navier-Stokes equations is developed and examined for the solution of fluid-structure interaction (FSI) problems. Newtonian viscous fluids under isothermal conditions are considered, and the Murnaghan-Tait equation of state is employed for the evaluation of mass density changes with pressure. A pressure-based approach is adopted to handle the low Mach number regime, ie, the pressure is chosen as primary variable, and the divergence-free condition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…27 Since then, it has been widely used and become a standard technique to handle moving domains in fluid-structure interaction (FSI) simulations. [28][29][30] More recent FSI simulations relying on this approach are presented in the work of Spenke et al, 31 La Spina et al, 32 and Liu et al 33 Furthermore, EMUM has been used in the context of free-surface flows 34 and to update finite element meshes according to prescribed boundary displacements. 35 The four-dimensional extension of EMUM (4DEMUM) presented in Section 3 allows us to obtain boundary-conforming pentatope meshes of complex geometries.…”
Section: F I G U R Ementioning
confidence: 99%
“…27 Since then, it has been widely used and become a standard technique to handle moving domains in fluid-structure interaction (FSI) simulations. [28][29][30] More recent FSI simulations relying on this approach are presented in the work of Spenke et al, 31 La Spina et al, 32 and Liu et al 33 Furthermore, EMUM has been used in the context of free-surface flows 34 and to update finite element meshes according to prescribed boundary displacements. 35 The four-dimensional extension of EMUM (4DEMUM) presented in Section 3 allows us to obtain boundary-conforming pentatope meshes of complex geometries.…”
Section: F I G U R Ementioning
confidence: 99%
“…Equation (4) has been considered for numerical simulations of weakly compressible flows in long tubes, such as waxy crude oil [52] and polymer extrusion [50]. Though equation ( 4) is very attractive for its simplicity, other pressure-density relations have been used in literature, like the Murnaghan-Tait model [32].…”
Section: Governing Equationsmentioning
confidence: 99%
“…This represents a popular partitioned scheme for the solution of FSI problems and it has been used and analyzed for instance in [8,31]. In [32] it has moreover been shown that the introduction of a weak compressibility in the fluid field alleviates the constraints of the instability condition of the artificial added mass effect and, in comparison to a fully incompressible solver, it reduces the number of coupling iterations required and it leads to an increase of the dynamic relaxation parameter.…”
Section: A Partitioned Dirichlet-neumann Algorithm For the Hdg-cg Cou...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, it has been widely used and become a standard technique to handle moving domains in fluid-structure interaction (FSI) simulations [27,28,29]. Also, very recent FSI simulations rely on it [30,31,32]. Furthermore, EMUM has been used in the context of free-surface flows (for example in [33]) and to update finite element meshes according to prescribed boundary displacements (for example in [34]).…”
Section: Introduction and Problem Definitionmentioning
confidence: 99%